Pengembangan Community Based Tourism di Desa Sarawet Kecamatan Likupang Timur Kabupaten Minahasa Utara - Jemmy Pangemanan; Silvana Wewengkang; Altje Tuwaidan; Diane Tangian (PolimdoSains, 2022)
Sarawet Village is located in the East Likupang sub-district, has a natural beauty that can be developed as a marine tourism object. There are manggrove forests, and coral reefs that are attractive for tourists to carry out tourism activities such as exploring mangrove forests, canoes, snorkeling and diving. In addition, Sarawet Village also has interesting historical, artistic and cultural values ​​to support tourism activities. Seeing the existing tourism potential, the central government set Likupang as one of the priorities for developing national-scale tourist destinations by being designated as a Special Economic Zone (SEZ). The Sarawet Village Government, in an effort to support the program, is currently developing a mangrove tourism destination using village fund allocations. In the management of tourism involves aspects that support the success of tourism, such as physical or geographical aspects, tourism attractiveness, accessibility, activities, facilities, accommodation, human resources, promotion, regulation, socio-cultural and economic. All of these aspects have a very important role, they are interconnected and influence each other. The application of CBT-based tourism is an approach to tourism development with participatory planning. What is meant by CBT is tourism that involves local communities by providing opportunities to manage and develop tourism, either directly or indirectly that has links with industry or tourism businesses, so that the distribution of profits is evenly distributed to communities in rural / coastal areas and small islands. The problem that occurs today is that public knowledge about tourism and how to manage the existing potential is still very low. Based on the foregoing, this study aims to analyze the potential of tourism objects, examine the participation of local communities in the management of tourism objects in an effort to improve the economy and welfare, then determine a CBT-based management strategy. This research is a descriptive study where the data obtained are tabulated and then described. Keywords : Tourism, Community based Tourism, Tourism potential